To the question of prospects for further constitutional and legal support of the principle of powers separation efficient functioning - Tsikavenka, Volha A. (Journal of the Belarusian State University. Law, 2023)
The article considers and suggests possible prospects for further improvement of the constitutional and legal foundations, in particular those relating to the provision of human rights and freedoms by the state and the implementation of state powers separation principle in the present realities. The features of the institution of the commissioner for human rights are studied on the example of the legislation of foreign countries. The ways of strengthening the executive branch of power, as well as expanding parliamentary control in the state, the participation of the parliament in the formation of the government are analysed.
Keywords: constitution; commissioner for human rights; the principle of separation of powers; local authorities; parliamentary control